Injectable in-situ curable hydrogel for medullary cavity hemostasis - Meng, Xiangxiao; Liu, Fei; Shi, Chao; Dou, Yichun; Zhang, Jingshuang; Jiang, Xieyuan; Shi, Rui (Frontiers in Bioengineering and Biotechnology, 2025)
Achieving hemostasis in the narrow and elongated medullary cavity is a challenge in bone hemostasis. This study developed an in-situ hemostatic hydrogel based on the Schiff base reaction principle, which was cross-linked by the aldehyde groups of dialdehyde-functionalized PEG (DF-PEG) and the amino groups of carboxymethyl chitosan/thrombin (CMCS/Th). We utilized the injectability and rapid curing capability of the hydrogel to achieve hemostasis through physical occlusion of the wound. Gel10 possessed an interpenetrating porous structure and cationic groups, with a water absorption capacity of approximately 269%. The resulting Gel10 can promote the aggregation of blood cells by adsorbing blood. Furthermore, Gel10 was successfully modified with thrombin to create Gel10-Th200, which enhanced mechanical properties and promoted secondary hemostasis and bone tissue repair. In a rabbit model of medullary cavity hemorrhage, compared with the control group (medical gauze) which required external pressure, Gel10-Th200 showed remarkable performance. It significantly shortened the bleeding time and reduced blood loss. Moreover, thanks to its enhanced in situ hardness, Gel10-Th200 did not require external compression. Additionally, Gel10-Th200 exhibited excellent cell compatibility and negligible hemolytic effects. In summary, Gel10-Th200, with its favorable shape adaptability and rapid curing ability, is considered a promising option for hemostasis in this complex bleeding site within the medullary cavity.